2009
DOI: 10.1104/pp.109.145656
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis Tandem Zinc Finger Protein AtTZF1 Traffics between the Nucleus and Cytoplasmic Foci and Binds Both DNA and RNA        

Abstract: Processing bodies (PBs) are specialized cytoplasmic foci where mRNA turnover and translational repression can take place. Stress granules are related cytoplasmic foci. The CCCH tandem zinc finger proteins (TZFs) play pivotal roles in gene expression, cell fate specification, and various developmental processes. Human TZF binds AU-rich elements at the 3# untranslated region and recruits decapping, deadenylation, and exonucleolytic enzymes to PBs for RNA turnover. Recent genetic studies indicate that plant TZFs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
240
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(249 citation statements)
references
References 97 publications
7
240
0
2
Order By: Relevance
“…One of RR-TZF proteins, AtTZF1, can bind to both DNA and RNA in vitro and colocalizes with P-bodies and SGs under certain stress conditions. 14 In this study, we demonstrated that VOZ2 colocalized with both SGs and P-bodies under heat stress conditions (Fig. 3).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…One of RR-TZF proteins, AtTZF1, can bind to both DNA and RNA in vitro and colocalizes with P-bodies and SGs under certain stress conditions. 14 In this study, we demonstrated that VOZ2 colocalized with both SGs and P-bodies under heat stress conditions (Fig. 3).…”
Section: Discussionmentioning
confidence: 78%
“…18 We speculated that the VOZ2 foci formed under the heat stress conditions were associated with SGs or P-bodies. To confirm that VOZ2 colocalizes with PABP8 and DCP1, 14 marker proteins of SGs and P-bodies, respectively, we generated transgenic Arabidopsis plants expressing both tagRFP-PABP8 or tagRFP-DCP1 and GFP-VOZ2 under the control of the CaMV35S promoter. Under normal temperature conditions, both tagRFP-PABP8 and GFP-VOZ2 were dispersed throughout the cytosol, whereas after the incubation at 42 C, the cytoplasmic granular structures of tagRFP-PABP8 and GFP-VOZ2 were formed after 20 min under the hightemperature condition, and the 2 types of granular structures merged completely (Fig.…”
Section: Voz2 Is Associated With Sgs Under the High-temperature Condimentioning
confidence: 99%
See 1 more Smart Citation
“…30,34,35 The involvement of DCP1, DCP2 and VCS in miRNA-mediated gene silencing has also been suspected in plants: AGO1 and DCP1 co-localize in protoplasts. 36 Moreover, VCS is involved in miRNA-mediated translational repression. 37 However, the role of decapping in the miRNA pathway remains unclear in plants.…”
Section: Introductionmentioning
confidence: 99%
“…Co-localization of DCP1 and AGO1 in P-bodies supports this hypothesis. 36 To find the common feature for class I miRNAs, we looked for the differences in structures between class I and class II miRNAs in terms of pri-miRNA framework, miRNA length, terminal base or 5' mRNA fragment after targeted by miRNA. However we could not find any common features for class I miRNAs.…”
Section: Introductionmentioning
confidence: 99%